Tourism and development in the developing world - Telfer, David J.; Sharpley, Richard 1956- (Routledge perspectives on development, 2008)
Tourism is widely considered as an effective contributor to socio-economic development, particularly in less developed countries. However, despite the almost universal adoption of tourism as a developmental option, the extent to which economic and social development inevitably follows the introduction and promotion of a tourism sector remains the subject of intense debate. The purpose of this book, therefore, is to provide an introduction to the tourism-development process. Focusing specifically on the less developed world and drawing on contemporary case studies, it questions many assumptions about the role of tourism in development and, in particular, highlights the dilemmas faced by destinations seeking to achieve development through tourism.